Pengalihwujudan dalam Kerangka Konsep Hukum Hak Cipta - Besar Besar (Bina Nusantara University, 2012)
Power of human intelligence and reasoning power as God's creation that has such a great ability and accompanied with such advanced technology to create or creation something, make something that is often beyond the limits of existing rules at the level of human life itself. The result of creativity and creations that appear either truly original creation or a form can not be separated from adaptations of copyright law. Copyright laws are made with the intent to regulate and protect the rights, in fact, considered to still have the weakness, therefore this paper tries to lift the adaptations within the framework of copyright law. In this article the author uses qualitative and descriptive methods are based on secondary data. From the results have not been found the regulations or laws that specifically deal about adaptations